Concerns of earthquake survivor mothers for their children and the role of school leadership in addressing them - Taner Derman, Meral; Türen, Şeyma (Frontiers in Public Health, 2025)
IntroductionThis study aims to examine the change in the concerns of mothers with preschool children before and after the earthquake and the role of school administrators in relieving these concerns. Understanding these concerns is essential for improving post-disaster support strategies for families.MethodsThe research was carried out in a holistic multi-case study design, which is one of the qualitative methods, with a study group consisting of 20 mothers and 5 school administrators living in the temporary housing area in Hatay. The data were collected through semi-structured interview forms and analyzed by content analysis method.ResultsThe findings showed that games and entertainment activities were at the forefront of mother–child relationships, but they were also a reflection of the earthquake. It has been revealed that mothers’ future plans focused on positive goals such as their children growing up in a healthy environment before the earthquake and becoming successful individuals by receiving a good education, but after the earthquake, these plans were negatively affected due to financial and social losses, uncertainties and disruptions in education. It has been shown that mothers had general concerns about the education, security and social development of their children before the earthquake, but these concerns became more concrete and intense after the earthquake. Mothers reported serious concerns, particularly about living conditions, psychological effects, education, and the future. School administrators, on the other hand, resorted to methods such as summer schools, social activities, guidance services and financial support to alleviate the concerns of mothers. They suggested improving housing conditions, opening vocational courses, strengthening infrastructure and involving psychosocial support teams.ConclusionThe research emphasized that the physical, social and psychological effects of natural disasters on individuals are multidimensional and revealed the critical role of school administrators in crisis management. It also highlights the need for coordinated efforts between families and schools in navigating post-disaster challenges.